Cardiovascular risk factors in Mexican American adults: a transcultural analysis of NHANES III, 1988-1994. - Sundquist, J (1999)
OBJECTIVES: This study examined the extent to which cardiovascular disease risk factors differ among subgroups of Mexican Americans living in the United States. METHODS: Using data from a national sample (1988-1994) of 1387 Mexican American women and 1404 Mexican American men, aged 25 to 64 years, we examined an estimate of coronary heart disease mortality risk and 5 primary cardiovascular disease risk factors: systolic blood pressure, body mass index, cigarette smoking, non-high-density lipoprotein cholesterol, and type 2 diabetes mellitus. Differences in risk were evaluated by country of birth and primary language spoken. RESULTS: Estimated 10-year coronary heart disease mortality risk per 1000 persons, adjusted for age and education, was highest for US-born Spanish-speaking men and women (27.5 and 11.4, respectively), intermediate for US-born English-speaking men and women (22.5 and 7.0), and lowest for Mexican-born men and women (20.0 and 6.6). A similar pattern of higher risk among US-born Spanish-speaking men and women was demonstrated for each of the 5 cardiovascular disease risk factors. CONCLUSIONS: These findings illustrate the heterogeneity of the Mexican American population and identify a new group at substantial risk for cardiovascular disease and in need of effective heart disease prevention programs.